The influence of self-esteem and self-consciousness on self-presentation among adolescent social media users - Sa'diyah, Siti Alifatus; Fauziyah, Nailatin (Indigenous, 2021)
This study aims to determine the effects between self-esteem and self-consciousness towards online self-presentation of adolescents who used social media. This is a quantitative correlational approach study that collecting data using three scales which are Presentation of Online Self Scale (POSS), State Self-Esteem Scale (SSES) and Self-consciousness Scale (SCS-R). The subjects of this study were 153 adolescents in senior high school in Lamongan. This place is chosen based on survey that shows all the student is using media social. That survey is also says that most of them doing online self presentation such as editing photo or make an quote before upload something in their social media. Data in this study is being collected using cluster sampling technique and  analyzed using multiple regression analysis. The results of this study show that self-esteem had negative effects towards online self-presentation of adolescent. Meanwhile, self-consciousness had no effects towards online self-presentation of adolescent. The final result indicated that self-esteem and self-consciousness had simultaneous effects toward online self-presentation of adolescent about 12,2%.Penelitian ini bertujuan untuk mengetahui pengaruh antara self-esteem dan self-consciousness terhadap self-presentation remaja pengguna media sosial. Penelitian ini merupakan penelitian kuantitatif korelasional dengan menggunakan alat pengumpulan data berupa Presentation of Online Self Scale (POSS), State Self-Esteem Scale (SSES) dan skala Self-consciousness Scale (SCS-R). Penelitian ini dilakukan di salah satu SMA di Lamongan dengan subjek berjumlah 153 orang. Tempat ini dipilih berdasarkan survey yang menunjukan bahwa semua siswa menggunakan media sosial. Survey juga menunjukan bahwa siswa melakukan teknik presentasi diri di media sosial seperti editing foto atau mempersiapkan kutipan kata sebelum mengupload sesuatu di sosial media. Penelitian ini menggunakan teknik pengambilan data cluster sampling dan data dianalisis menggunakan teknik analisis regresi ganda. Hasil dari penelitian ini menunjukkan bahwa terdapat pengaruh signifikan yang bersifat negatif antara self-esteem dengan self-presentation remaja pengguna media sosial. Sementara itu, pada self-consciousness dengan self-presentation tidak terdapat pengaruh siginifikan. Di sisi lain, secara bersama-sama self-esteem dan self-consciousness berpengaruh signifikan dengan self-presentation remaja pengguna media sosial. Sumbangan efektif yang diberikan self-esteem dan self-consciousness secara bersama-sama dengan self-presentation adalah sebesar 12,2% dan sisanya dipengaruhi oleh faktor lain.